Variation in Bacterial and Eukaryotic Communities Associated with Natural and Managed Wild Blueberry Habitats - Svetlana N. Yurgel; Gavin M. Douglas; André M. Comeau; Melissa Mammoliti; Ashley Dusault; David Percival; Morgan G. I. Langille (Phytobiomes Journal, 2017)
We examined the differences between bacterial and eukaryotic soil communities associated with natural and managed habitats of wild blueberry, Vaccinium angustifolium. In total, 138 bacterial and 130 eukaryotic soil and rhizosphere communities across seven blueberry fields, all established at least 30 years ago and from two forest areas adjacent to some of these fields, were analyzed. We analyzed correlations between soil chemical factors and the structure of eukaryotic and bacterial communities, including differences in the microbiome between bulk and rhizosphere soils, and between rhizospheres of plants growing in natural and managed habitats. Characterization of a broad selection of fields across the province of Nova Scotia, Canada, allowed us to tentatively identify specific signatures from several distinct soil niches. Our data indicate that bacterial and eukaryotic communities differ in how they correlate with soil chemical properties. Also, while eukaryotic communities correlate stronger with soil fertility than bacterial communities, plant selection had a stronger effect on bacterial microbiomes than on eukaryote microbiomes. Additionally, we found that the composition of root-associated bacterial communities differs between managed and natural wild blueberry habitats, confirming previous reports that management can affect rhizosphere microbiomes.